Penyelesaian Sengketa Kontrak Antara Pemerintah Kabupaten Buleleng Dengan PT. Chandra Dwipa Terkait Pembangunan Ruang Terbuka Hijau Taman Bung Karno Singaraja - Ayu Apsari Hadi, I Gusti; Febrinayanti Dantes, Komang (Jurnal Komunikasi Hukum, 2021)
This study aims to determine the form of dispute resolution between the Buleleng Regency Government and the private sector PT. Candra Dwipa regarding the construction of RTH Bung Karno Park, Singaraja city. The data collection technique used purposive sampling through interviews, observation, documentation and literature study. The subjects in this study were the Regional Government, especially the Commitment Making Official (PPK) of the Disperkimta, Buleleng Regency. Data processing and analysis techniques in this study will be carried out qualitatively. After the qualitative analysis process is carried out, then the data will be presented in a descriptive qualitative manner and systematically. The results showed that (1) a contract clause / agreement letter between the Buleleng Regency Government and PT. Chandra Dwipa is in accordance with the pacta sunt servanda principle and has implications for the rights and obligations of the parties, namely the DISPERKIMTA party can supervise the work of the provider and the provider must carry out the work according to the applicable contract; (2) the dispute settlement mechanism for the development of RTH Taman Bung Karno in which the provider (contractor) does not fulfill the work as planned, namely the realization is only 74,932% while the deviation is -25,068%, the government will stop work, impose fines, and put the provider into in the Black List.